Improving logistics and Supply Chain efficiency in the oil and Gas Sector - A literature review - A Literature Review - SAIF ALI SAIF AL JARADI,; Dr. Naim Ayadi, (IJRDO - Journal of Business Management, 2025)
The oil and gas (O&G) sector face unique logistical and supply chain challenges due to its complex, capital-intensive, and high-risk operations. Efficiency in logistics and supply chainmanagement (SCM) is critical for reducing costs, ensuring timely operations, and maintaining competitive advantage. This literature review synthesizes current research on methods andstrategies to enhance logistics and supply chain efficiency in the O&G industry. It highlights the adoption of digital technologies, supply chain integration, lean practices, risk management, and sustainability efforts. The review concludes with gaps in literature and suggestions for future research.